The Analysis of Distributed Two-Layers Components in Three-Layer Planar Structure (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2018)
The algorithms for analyzing of two-layer distributed discontinuities in the form of an inductive section in a microstrip transmission line and an H-shaped slot resonator with a transverse arrangement of "dumbbells" in its ground plane by the transverse resonance method are improved and developed. This method includes the mutual coupling of components that make up the discontinuity. According to the analysis results, the considered discontinuity is a multifunctional device and has scattering characteristics that contain simultaneously signal transmission and rejection. At this the two-layer discontinuity provides a wideband (up to 40 %) rejection with two-frequency characteristic of resonant reflection, and forms either two narrowband passband filters (about 3 %), or one wideband (up to 10 %) passband.